Epicardial catheter-based ventricular reconstruction (ECVR) in a patient with ischemic heart failure and an anteroapical aneurysm. Issue 2 (April 2015) - Van Praet, K.; Stockman, B.; Vanderheyden, M.; Bartunek, J.; Casselman, F.
Abstract : Extended anterior myocardial infarction (MI) is frequently followed by left ventricular (LV) remodeling ensuing in heart failure and aneurysmatic transformation of the infarcted myocardial segment. Therapies that attenuate or reverse pathological LV remodeling have been shown to improve functional status and outcomes. This case reports our recent experience with a catheter based technique for ventricular restoration.